2005
DOI: 10.1093/ps/84.8.1222
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broiler chickens fed diets supplemented with a direct-fed microbial

Abstract: From hatch to 18 d of age broilers were fed starter diets with (0.9 kg/ton) or without direct fed microbial (DFM). At 18 d, birds were weighed and, within DFM treatment (trt), randomly assigned to battery pens. In Exp 1, a 2 x 2 factorial arrangement of nutrient density [control (C, 19.3% protein (CP), 0.84%, Ca 0.37% nonphytin P (nPP); and 17.1% CP, 0.8% Ca, and 0.3% nPP in the grower (Gr) and finisher (Fn) diets, respectively) and moderate (M) (17% CP, 0.69% Ca, 0.30% nPP; 15% CP, 0.66% Ca, 0.25% nPP in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 20 publications
6
49
0
Order By: Relevance
“…Generally, there are inconsistencies in reports in the literature on the beneficial effects of probiotics and organic acids on broiler growth performance. Angel et al (2005) recorded that under favourable rearing conditions, without disease or stress, dietary supplementation with probiotics had no beneficial effects on broiler growth performance. In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, there are inconsistencies in reports in the literature on the beneficial effects of probiotics and organic acids on broiler growth performance. Angel et al (2005) recorded that under favourable rearing conditions, without disease or stress, dietary supplementation with probiotics had no beneficial effects on broiler growth performance. In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds.…”
Section: Resultsmentioning
confidence: 99%
“…Organic acids, probiotics and prebiotics have been shown to reduce serum cholesterol and the abdominal fat of broiler chickens (Yusrizal & Chen, 2003;Gaggia et al, 2010), increase performance, improve resistance to pathogenic bacteria colonization and enhance host mucosa immunity, resulting in reduced pathogen load and improved health status of the animal (Yalcinkaya et al, 2008). Angel et al (2005), Yang et al (2008) and Pirgozliev et al (2008) reported beneficial effects of dietary additives such as organic acids and probiotics on energy and protein utilization in poultry. Some studies have been conducted to determine the effects of these feed additives on growth indices, serum biochemical parameters and carcass characteristics of broiler chickens (Ashayerizadeh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Working with broilers, Angel et al (2005) demonstrated that the addition of probiotics based on Lactobacillus (0.9kg/ton) in feed has improved the retention of calcium and phosphorus by birds receiving feed that supply to their nutritional demands. However, birds receiving moderate density (18% less calcium and phosphorus in relation to the recommendation of the National Research Council -NRC) and low density feed (25% less calcium and phosphorus in relation to the recommendation by NRC) supplemented with probiotics presented bone breaking resistance and ash concentration in tibia similar to those receiving the control feed, without addition of additive.…”
Section: Bone Quality In Broilersmentioning
confidence: 99%
“…Also, their positive effects on protein utilization have been indicated. Angel et al (2005) found that broilers fed diets containing lower levels of nutrients (protein, calcium and available phosphorus) had poorer performance than the control group, but supplementation of those diets with probiotic, improved nutrients retention and thus prevented their negative effects. In another study, it was shown that supplementation with a prebiotic, improved the performance of broilers fed with LPD (Torres-Rodriguez et al, 2005).…”
Section: Introductionmentioning
confidence: 97%